2016
DOI: 10.7841/ksbbj.2016.31.3.158
|View full text |Cite
|
Sign up to set email alerts
|

Mass Cultivation and Secondary Metabolite Analysis of Rhodobacter capsulatus PS-2

Abstract: Plant growth promoting (PGP) hormones, which are produced in a small quantity by bacteria, affect in plant growth and development. PGPs play an important role on the crop productivity in agricultural field. In this study, a photosynthetic bacterial strain producing the PGP was isolated from paddy soil. Bacterial isolate was gram negative, rod-shaped and motility positive. From the 16s rRNA gene sequence analysis, the isolate was identified as Rhodobacter capsulatus PS-2. The mass cultivation of R. capsulatus P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Rhodobacter capsulatus PS-2, which was isolated from paddy soil, was capable of producing a large amount of IAA (197.44 ± 5.92 mg/L) in an optimal medium containing 0.3% tryptophan. [103]. Recently, Kang and colleagues also reported that R. sphaeroides KE149 could produce 4.6-5.3 µg/mL of IAA in the presence of D-tryptophan in medium and was able to alleviate the adverse effect of water stress for adzuki bean plants [78].…”
Section: Indole-3-acetic Acid (Iaa) Production By Pnsbmentioning
confidence: 98%
“…Rhodobacter capsulatus PS-2, which was isolated from paddy soil, was capable of producing a large amount of IAA (197.44 ± 5.92 mg/L) in an optimal medium containing 0.3% tryptophan. [103]. Recently, Kang and colleagues also reported that R. sphaeroides KE149 could produce 4.6-5.3 µg/mL of IAA in the presence of D-tryptophan in medium and was able to alleviate the adverse effect of water stress for adzuki bean plants [78].…”
Section: Indole-3-acetic Acid (Iaa) Production By Pnsbmentioning
confidence: 98%
“…Among PNSB isolated from various paddy fields, R. palustris produces plant growth-promoting substances, ammonium, ALA, and indole-3-acetic acid (IAA); reduces methane emission from a mixture of soil slurry and ground rice straw; and removes Cd and Zn from the heavy metal-supplemented medium, whereas R. gelatinosus produces ammonium, ALA, and IAA and removes Cd and Zn [109]. R. capsulatus isolated from paddy soil produces carotenoids and IAA [110].…”
Section: Isolations Of Pnsb From Rice Fieldsmentioning
confidence: 99%